2003
DOI: 10.1016/s1097-2765(03)00367-8
|View full text |Cite
|
Sign up to set email alerts
|

The BRCA2-Interacting Protein DSS1 Is Vital for DNA Repair, Recombination, and Genome Stability in Ustilago maydis

Abstract: DSS1 encodes a small acidic protein shown in recent structural studies to interact with the DNA binding domain of BRCA2. Here we report that an ortholog of DSS1 is present in Ustilago maydis and associates with Brh2, the BRCA2-related protein, thus recapitulating the protein partnership in this genetically amenable fungus. Mutants of U. maydis deleted of DSS1 are extremely radiation sensitive, deficient in recombination, defective in meiosis, and disturbed in genome stability; these phenotypes mirror previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
115
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(125 citation statements)
references
References 25 publications
10
115
0
Order By: Relevance
“…In contrast, certain combined domains of BRCA2 promote Rad51-mediated strand exchange in vitro, suggesting that there may be intramolecular collaboration between distinct domains of BRCA2 [140,161]. The U. maydis BRCA2 homolog, Brh2, possesses only one BRC domain and has been purified with DSS1 in vitro [20,25,141]. Brh2/DSS1 efficiently catalyzes the loading of Rad51 onto the free 5′ end of a dsDNA-ssDNA junction, provided that the ssDNA is pre-coated with RPA (as it would be in vivo).…”
Section: Molecular Functions Of Brca1 and Brca2mentioning
confidence: 99%
“…In contrast, certain combined domains of BRCA2 promote Rad51-mediated strand exchange in vitro, suggesting that there may be intramolecular collaboration between distinct domains of BRCA2 [140,161]. The U. maydis BRCA2 homolog, Brh2, possesses only one BRC domain and has been purified with DSS1 in vitro [20,25,141]. Brh2/DSS1 efficiently catalyzes the loading of Rad51 onto the free 5′ end of a dsDNA-ssDNA junction, provided that the ssDNA is pre-coated with RPA (as it would be in vivo).…”
Section: Molecular Functions Of Brca1 and Brca2mentioning
confidence: 99%
“…Interestingly, a DSS1 ortholog in Ustilago maydis has been found to associate with a BRCA2-related protein, Brh2 (Kojic et al, 2003). Deletion of DSS1 from U. maydis has been shown to result in radiation hypersensitivity, recombination deficiency, meiosis defect, and genomic instability, similar to the phenotype of Brh2 and Rad51 deletion in U. maydis (Kojic et al, 2003). In addition, the yeast ortholog of DSS1, sem1p, regulates exocytosis and pseudohyphal differentiation (Jantti et al, 1999).…”
Section: Introductionmentioning
confidence: 96%
“…While Brca2 was known to localize on the meiotic chromosomes during the formation of the synaptonemal complex in human (Chen et al, 1998a), the interaction disclosed between Brca2 and Dmc1 in Arabidopsis (Arabidopsis thaliana) helped assign a role for Brca2 at meiosis (Siaud et al, 2004). Another interactant of Brca2, Dss1, was uncovered (Marston et al, 1999), the depletion of which leads to a brca2-like phenotype in Ustilago or mouse (Kojic et al, 2003;Gudmundsdottir et al, 2004). Its yeast (Saccharomyces cerevisiae) counterpart, Sem1, is found associated with the 19S proteasome, but it also participates in the resistance to genotoxic treatment (Funakoshi et al, 2004;Krogan et al, 2004), although no Brca2-like protein can be identified in yeast.…”
mentioning
confidence: 99%